DEVELOPING STUDENTS WORKSHEET FOR READING COMPREHENSION OF DESCRIPTIVE TEXT USING KAHOOT FOR TENTH GRADE STUDENTS AT SMA DHARMA PANCASILA MEDAN - Shielvy Indah Mentari; Rafika Dewi Nasution; Ade Aini Nuran (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2019)
The aim of this study was to develop students worksheet for reading comprehension of descriptive text using Kahoot! for tenth grade students at SMA Dharma Pancasila Medan. This study was categorized as Research and Development (R&D) through six stages: gathering data and information, conducting need analysis, designing first form of media, validating by experts, revising media and final product. The subject of the study was the tenth grade students of SMA Dharma Pancasila Medan with the instruments of collecting data were interview and questionnaires. The result of the study was platform Kahoot! to be used as stusents worksheet for reading comprehension of descriptive text. In the percentage form, the average score of experts’ validation in term of content aspect was 94.2%, presentation aspect was 94%, language aspect was 97% and graphic aspect was 100%. These scores were categorized “Very Good”.  It means the developing students worksheet for reading comprehension by using Kahoot! was appropriate for tenth grade students of SMA Dharma Pancasila Medan.Keywords: Descriptive text, students worksheet, Kahoot!